PENINGKATAN HASIL BELAJAR MATERI TEKS EKSPLANASI MELALUI MODEL PENDEKATAN SCIENTIFIK - Ulfa Anggraini (Universitas Wijaya Kusuma Surabaya, 2020)
Research applies a learning model with a scientific approach to learning. It is hoped that by applying a learning model with a scientific approach in learning, students will be more active so that their learning outcomes will increase. This study used a Classroom Action research design. The use of the scientific approach learning model can improve student learning outcomes achieving a class average score of 83 with a percentage level of completeness of 83.3% in Indonesian language learning on the material